Treatment of Bilateral Varicocele and Other Scrotal Comorbidities Using a Single Scrotal Access: Our Experience on 34 Patients. (22nd July 2014) - Iacono, F.; Ruffo, A.; Prezioso, D.; Romeo, G.; Illiano, E.; Di Lauro, G.; Romis, L.; Sansalone, S.
Abstract : Introduction . Varicocele is the main cause of infertility in male and the most correctable cause of it too. In this study, we present our experience on 34 patients affected by bilateral varicocele and other scrotal comorbidities treated underwent surgery with a scrotal access. Materials and Methods . 34 patients were enrolled with clinical palpable and infraclinical (ultrasonic doppler scanning) bilateral varicocele and other comorbidities like right hydrocele, left hydrocele, bilateral hydrocele, and epididymal cyst. They all underwent scrotal bilateral varicocelectomy under local anesthesia. Results and Discussion . At 6 months, no other complications were reported. No case of testicular atrophy was observed. None had recurrence of varicocele. All scrotal comorbidities were treated as well. Conclusion . Scrotal access with local anesthesia is a safe and useful technique to treat patients with bilateral varicocele and other scrotal comorbidities.